STUDENTS’ STRUCTURAL AND CULTURAL PROBLEMS IN TRANSLATING FROM INDONESIAN INTO ENGLISH - Bahrul Ulum (JARES (Journal of Academic Research and Sciences), 2016)
This study is aimed at evaluating the lexical, grammatical and cultural problems faced by students of translation subjects in translating from Indonesian into English. The subjects of this study were students with low average ability. The findings show that students have problems in translating lexical, grammatical and cultural items. Based on the results of the analysis, it can be concluded that the problems are caused by low mastery of lexis, grammar and culture. It is recommended that the lecturers of translations give attention to these three aspects. Â Keywords: Translation, lexis, grammar, culture. Â Received: 10 June, 2016; Accepted: 8 September, 2016